An Assessment of the Exchange Rate Pass-Through in Angola and Nigeria - Lariau, Ana (IMF Working Papers; Working Paper ;, 2016)
This paper estimates the exchange rate pass-through to consumer price inflation in Angola and Nigeria, with particular emphasis on the changes of the pass-through over time. Even though the two countries share smilar dependence on oil exports, this paper reveals different results. For Angola, the long-run exchange rate pass-through to prices is high, though it has weakened in recent years reflecting the de-dollarization of the economy. In Nigeria, there is no stable long-run relationship between the exchange rate and prices, and changes in the exchange rate do not have a significant pass-through effect on inflation. However, the passthrough effect on core inflation is significant.